Democracy and the justification of political authority - Chen, L (2015)
This thesis investigates the place of democracy in the justification of political authority. The investigation of the thesis proceeds in two parts. The first part considers the lines of argument that being democratic is necessary for political authority to be fully justified. Anna Stilz argues that the subjects have general obligation to obey the law only if they are free from political domination, which freedom is available only in the democratic State. Philip Pettit argues that the freedom from domination does not affect the subjects' obligation to obey the laws, but is constitutive of their obligation to 'accept a regime', i.e. to refrain from revolting against a regime. David Estlund argues that the State's right to enforce the laws is justified independently of its capacity to obligate the subjects to obey the laws, and that the former right is uniquely conditional on the political decision-procedures' being democratic. Thomas Christiano argues that it is the ruler's 'right to rule', i.e. a claim-right correlative with the subjects' obligation to obey, which turns on the existence of a democratic assembly. These arguments fail to make sufficient room for the fundamental principle of political authority: as outlined in John Finnis's argument, political authority is required for the solution of a community's co-ordination problems for the common good, and it is to be exercised by those who have efficacious capacity to do so. Democracy does not change what it is to be justified authority in accordance with the fundamental principle. The second part supplements the fundamental principle by identifying two important ways in which democracy bears on the legitimacy of the State. First, democracy affects political legitimacy if and only if democracy is viable in the relevant community. Secondly, it is the laws that regulate legal change—as distinct from laws that regulate other official and social conduct—that depend for their authority on democracy.